2021
DOI: 10.3390/su13063163
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Employee Empowerment and Organizational Commitment on Workforce Sustainability

Abstract: Building and maintaining a sustainable workforce in the hospitality sector, where demand for talent consistently exceeds supply across the globe, has only been exacerbated by COVID-19. The need to sustain this workforce behooves the industry to unpack core drivers of employee commitment in order to retain top talent. This paper explores how dimensions of employee empowerment increase organizational commitment and, in turn, reduce turnover intention—leading to a more sustained workforce. Drawing on the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 58 publications
(66 reference statements)
2
22
0
1
Order By: Relevance
“…Through employees empowerment, the organization gives the employee incentives and vision, herewith increasing motivation, productivity and performance. When employees feel empowered, they will often seek out new procedures and even products within an organization and encourage innovation (Murray & Holmes, 2021). Theoretically, employee empowerment and organizational agility can be linked through contingency theory (Rastegari et al, 2020;Read III, 2020;Segerman, 2020).…”
Section: Literature Review and Hypotheses Development Employee's Empowermentmentioning
confidence: 99%
“…Through employees empowerment, the organization gives the employee incentives and vision, herewith increasing motivation, productivity and performance. When employees feel empowered, they will often seek out new procedures and even products within an organization and encourage innovation (Murray & Holmes, 2021). Theoretically, employee empowerment and organizational agility can be linked through contingency theory (Rastegari et al, 2020;Read III, 2020;Segerman, 2020).…”
Section: Literature Review and Hypotheses Development Employee's Empowermentmentioning
confidence: 99%
“…Despite this fact, it is constantly growing, the hospitality industry faces its unique workforce challenge where employees’ turnover is extremely high ( Baum, 2008 ; Davidson et al, 2010 ). Building and maintaining a sustainable workforce and eliminating turnover intentions of organizational employees have turned into one of the foremost global issues confronted by hospitality organizations ( Yam et al, 2018 ; Murray and Holmes, 2021 ). Barron (2008) illustrated that the reputation of the hospitality industry as a key means of permanent employment is not good and holds a negative image for offering limited chances for career development.…”
Section: Introductionmentioning
confidence: 99%
“…In this severe situation, the negative mental health of employees undoubtedly affects the quality of tasks, thereby affecting corporate performance and business sustainability [14,[63][64][65]. Sasaki et al [14] concluded that the fear of COVID-19 and psychological distress could affect work satisfaction and turnover intention.…”
Section: Individual Levelmentioning
confidence: 99%